1998
DOI: 10.2108/0289-0003(1998)15[615:gdiajs]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Differentiation in a Japanese Stream-Breeding Frog, Buergeria buergeri, Elucidated by Morphometric Analyses and Crossing Experiments

Abstract: Hiroshima and Aomori populations of Buergeria buergeri (hereinafter abbreviated as HIROSHIMA and AOMORI, respectively) were morphologically differentiated in both sexually matured frogs and tadpoles. The mean snout-vent lengths of females were 67.4 mm in HIROSHIMA and 50.4 mm in AOMORI, and those of males were 42.9 mm in HIROSHIMA and 37.2 mm in AOMORI. The mean body weights of females of HIROSHIMA and AOMORI just after spawning were 18.0 g and 7.2 g, and those of males of HIROSHIMA and AOMORI were 4.9 g and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…We identified differences in the adaptation temparature for egg maturation and embryonic development between the Amami and Okinawa populations of O. ishikawae, which is a similar trend to that found in populations of Rana pipiens (Moore, 1946(Moore, , 1947 and Buergeria buergeri (Ueda et al, 1998). Based on our trials (data not shown), it was determined that the ideal temperatures for the ovulation and maturation of eggs, and the rearing of embryos and larvae are 18 and 20°C for frogs of the Amami and Okinawa populations, respectively.…”
Section: Discussionsupporting
confidence: 75%
“…We identified differences in the adaptation temparature for egg maturation and embryonic development between the Amami and Okinawa populations of O. ishikawae, which is a similar trend to that found in populations of Rana pipiens (Moore, 1946(Moore, , 1947 and Buergeria buergeri (Ueda et al, 1998). Based on our trials (data not shown), it was determined that the ideal temperatures for the ovulation and maturation of eggs, and the rearing of embryos and larvae are 18 and 20°C for frogs of the Amami and Okinawa populations, respectively.…”
Section: Discussionsupporting
confidence: 75%
“…Tadpoles of the new species were fixed in 10% formalin. A set of 13 characters of preserved adult specimens and head-body length of preserved tadpole specimens were measured to the nearest 0.05mm with dial calipers by mainly following the study of Ueda et al (1998). Ten of the earlier mentioned characters are snout-vent length (SVL), head width (HW), head length (HL, in parallel with the line connecting angle of jaw), eye distance (ED), tympanum diameter (TD), distance between tympanum and eye (T-ED), interorbital distance (IOD), snout length (SL, in parallel with the line connecting angle of jaw), tibia length (TIBIA) and internarial distance (IND).…”
Section: Methodsmentioning
confidence: 99%
“…Azevedo, French & Partridge, 1997;Banerjee & Singh, 1998) as well as a few vertebrate species (e.g. Berven, 1982b;Pierce & Harvey, 1987;Harris, Fondecaro & Kasbohm, 1995;Ueda, Hasegawa & Marunouchi, 1998;Hansen & Boonstra, 2000).…”
Section: Introductionmentioning
confidence: 99%